Caracterização de lectinas de leguminosas por espectrometria de massa - Simões, Rafael da Conceição (2011)
Mass spectrometry is a technique widely used in all prod uctive sectors. Since the late '80s with the emergence of soft ionization techniques, mass spectrometry has been widely disseminated in the analysis of biopolymers such as fatty acids, nucleic acids, oligosaccharides and especially proteins. Lectins are proteins of nonimmune origin that have at least one specific and reversible binding carbohydrate domain, without the ability to modify them. These proteins are widely distributed in nature. Lectins isolated from seeds of legumes are among the most studied and have high homology degree, being an important molecular marker of evolution in this clade. This study aimed to characterize some legume lectins by m ass spectrometry. Lectin EVA and LAA with 240 and 237 amino acid residues respectively, were analyzed for native mass and sequence of amino acids determined, showing a high degree of homology with other legume lectins. Lectin ConGF, a ConA-like, was analyzed for protein content in the crystal. Was determined that bot h mature chain and proteolytic fragments are present to form crystal, which indicates no difference between the chains structure covalently linked together by weak interactions. The partial sequence shows that ConGF has several structural features within the subtribe Diocleinae. All results demonstrate that mass spectrometry is a versatile and robust tool for characterizing proteins and can be successfully used to obtain structural information of lectins.